STUDY REGARDING DIFFERENT TYPES OF AUDITOR’S MISSIONS - Botez, Daniel (Studies and Scientific Researches. Economics Edition, 2013)
After the involvement of the audit profession in several financial scandals, the international body of the profession, International Federation of Accountants – IFAC, has developed and published a conceptual framework and reviewed most of the reference standards in auditing to provide references regarding the responsibility of the professionals and the extent of their missions. Thus was established the use of a general term for professionals, the “practitioner”, in the context of specific missions using the “auditor”, “practitioner” or “accountant”. On the other hand, have been revised professional standards establish insurance missions and non-insurance operations, with their specific missions that do not provide insurance, including the recoding. The use of these references by audit professionals constitutes one of the “keys” to their success.